The Logic of the Laws - Moyer, D.S (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 1975)
This study is directed towards providing basic background material for the understanding of South Sumatran social organisation. To this end, four legal codes from the first half of the nineteenth century are presented and analysed. The method used in the analysis is a modification of that used by Levi-Strauss for the analysis of myth.